DOI: 10.17077/etd.77ij2bp6
|View full text |Cite
|
Sign up to set email alerts
|

Development of chemically active metal oxide composite nanofiber filters for water treatment

Abstract: My friends and family, for supporting me throughout the tricky journey that is graduate school. Mom and Dad, thank you for always pushing me to keep going (and for the extra emotional support during the last month of writing my dissertation). Ann, thank you for always being "Ann." Edgard Verdugo, my husband and best friend. Thank you for your unconditional love and endless assistance. You made this experience exceed my wildest dreams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 156 publications
(222 reference statements)
0
3
0
Order By: Relevance
“…PTA-P25 adsorptive interactions may explain these observations. It has been reported that PTA chemisorbs onto surfaces of P25 nanoparticles to form bidentate ring complexes in water ( Figure 19) [71,72]. Accordingly, PTA would act as a stabilizing or "capping" ligand to help prevent the agglomeration of P25 during the electrospinning process [72].…”
Section: Figure 13mentioning
confidence: 99%
See 2 more Smart Citations
“…PTA-P25 adsorptive interactions may explain these observations. It has been reported that PTA chemisorbs onto surfaces of P25 nanoparticles to form bidentate ring complexes in water ( Figure 19) [71,72]. Accordingly, PTA would act as a stabilizing or "capping" ligand to help prevent the agglomeration of P25 during the electrospinning process [72].…”
Section: Figure 13mentioning
confidence: 99%
“…It has been reported that PTA chemisorbs onto surfaces of P25 nanoparticles to form bidentate ring complexes in water ( Figure 19) [71,72]. Accordingly, PTA would act as a stabilizing or "capping" ligand to help prevent the agglomeration of P25 during the electrospinning process [72]. Our observation of improved P25 dispersion is also consistent with previous work from our group, which demonstrated that the inclusion of PTA at 2.4 wt.% in a PAN precursor sol-gel improved the dispersion of TiO2 [72].…”
Section: Figure 13mentioning
confidence: 99%
See 1 more Smart Citation